Extent of Academic Achievement of Day and Boarding Secondary Schools Students in Anambra State, Nigeria - Ogechukwu, Dr Okoye Faith; Chika, Nnamani Patience (International Journal of Scientific Research and Management (IJSRM), 2018)
The study examined the extent of Academic Achievement of Day and Boarding Secondary Schools Students in Onitsha Education Zone of Anambra State. Three research questions guided the study and survey research design was adopted. Descriptive survey research design was used for the study. The population of the study consisted 850 teachers within Onitsha Education Zone in Anambra State. The sample size consisted 85 teachers and was selected using simple random sampling. The instrument used for data collection was questionnaire and the data collected were analyzed with mean. The findings revealed that boarding students academically achieve better than day students and that day students are distracted at home unlike boarding school students who are under the control of teachers for their study. It was concluded that lack of finance, educational facilities and inadequate infrastructures are the factors that affect the academic achievement of both the day and boarding students. The researchers recommended among others that students should be allowed to attend boarding schools so as to perform better and that government should intervene in schools by providing them with academic and boarding facilities